2012
DOI: 10.1093/annonc/mdr575
|View full text |Cite|
|
Sign up to set email alerts
|

Fertility and gonadal function in female survivors after treatment of early unfavorable Hodgkin lymphoma (HL) within the German Hodgkin Study Group HD14 trial

Abstract: Hormonal levels after 2+2 indicate a reduced ovarian reserve. However, 2+2 in combination with GnRH analogues does not compromise fertility within the evaluated observation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 30 publications
0
73
0
6
Order By: Relevance
“…Relevant to this highly debatable issue, Behringer et al [12] also found that the use of GnRHa during chemotherapy has significantly increased the probability to become pregnant (OR 5 12.87; p 5 .001). Similarly, Del Mastro et al [11] and the authors of several other recent meta-analyses of RCTs [1] concluded that the significant reduction (p 5 .013) in POF rate, associated with GnRHa, provides convincing evidence in support of the efficacy of this preventive strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant to this highly debatable issue, Behringer et al [12] also found that the use of GnRHa during chemotherapy has significantly increased the probability to become pregnant (OR 5 12.87; p 5 .001). Similarly, Del Mastro et al [11] and the authors of several other recent meta-analyses of RCTs [1] concluded that the significant reduction (p 5 .013) in POF rate, associated with GnRHa, provides convincing evidence in support of the efficacy of this preventive strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of evidence for recommending such strategies may be considered low, according to Fleisher et al [17], because it is based on nonrandomized, case-control, or observational studies. On the contrary, the role of GnRHa therapy in preserving ovarian function has been assessed both in randomized trials and in nonrandomized, case-control studies [1,3,5,8,9,[11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Однако при использовании программ с меньшими суммарными дозами алкили-рующих препаратов (2 цикла ВЕАСОРР-эск + 2 цикла ABVD) эффект защиты яичников возможен. Число беременностей оказалось выше в группе женщин, которым проводилась защита яичников во время хи-миотерапии [25]. Аналогичные результаты получены Ю.В.…”
Section: клиническая онкогематологияunclassified
“…Consistent with previous observations that AYA women in their 30s are more likely than younger women to develop chemotherapy-associated premature ovarian failure, AMH recovery following chemotherapy is more likely in younger, compared to older AYAs with a history of Hodgkin's lymphoma. 65 …”
Section: Measuring Ovarian Reserve: Anti-mullerian Hormonementioning
confidence: 99%